Aggregation Dynamics: From problems and solutions to a generalized ecology - van Vlijmen, Bas (Transmathematica, 2023)
Aggregation Dynamics is a generalisation of ecology where organisms are replaced by aggregations. This totalises the notion of the ecology of living things to the ecology of all things. Aggregations are defined recursively: a thing is an aggregation if an already recognised aggregation acts on it accordingly. The argument begins by problematising human notions of problem and solution. Reflection on this results in hypotheses such as the Innovation Illusion and the Control Illusion. Aggregation Dynamics suggests that behaviour and organisation of aggregations is emergent and largely information-driven. From that basis, the illusions seem plausible.